About some Belarusian features of dialects in northern Chernigov Region in connexion with their grouping problems - Зевако, Валентина Іванівна (Philological Studies: the Scientific Publication of Kryvyi Rih State Pedagogical University, 2014)
The article analyzes the phonetic features of Belarusian origin that form a specific current dialects of northern part of Novgorod-Seversky district in Chernihisk region and their influence on the determination of their place in the system of the Eastern Polissian dialect of the Ukrainian language.